The Creation of Painting Series “Isan Art Collection” - Waiyarabut, Rattana (Chophayom Journal, 2024)
The objectives of this research were 1) to study the themes related to the lifestyle and culture of Isan, the Northeastern region of Thailand, and 2) to create contemporary Isan Thai paintings in a semi-abstract style using acrylic on canvas. The initial inspiration for these creative works comes from personal experiences and impressions of Isan lifestyle and culture. The creative process for the series "Isan Art Collection" involves gathering documentary information, field imagery, and relevant artistic concepts to serve as a database for analyzing themes, forms, and techniques in traditional Thai painting. Two pieces of traditional Thai paintings will be created. The concept focuses on reflecting the unique identity of Isan Thai art. Initially, the ideas are conveyed through preliminary sketches, which are refined and simplified in form. The overall composition is arranged to align with the selected techniques and creative execution. The creation process reveals that the paintings encompass content related to Buddhist beliefs, reflecting the beauty and charm of the Isan lifestyle and local culture. This is presented through shapes, objects, and Buddhist art symbols that are simple yet reflect the wisdom and craftsmanship of local artisans. The technique employed is acrylic on canvas, utilizing methods of layering colors, dabbing, and overlapping multiple layers to create texture and depth, enhancing the visual interest of the works. The compositions are asymmetrically balanced, with focal points featuring larger shapes, while medium and smaller shapes are arranged as artistic elements according to their importance. This arrangement aims to create an aesthetic experience rich in imagination and creative thought. Keyword: Isan Art Collection, Isan Thai Art and Culture, Contemporary Isan Thai Painting